Human Rights in the Perspective of the Qur'an - Nurindah Sari; Muhammad Alfan (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss human rights in the view of the Qur'an. The research method used in the study uses qualitative research through literature review by applying this analysis and using a thematic interpretation approach. The discussion of this research includes general views on human rights, the views of the Koran on human rights, and the implementation of the verses of the Koran regarding human rights. This study concludes that the Koran views the concept of human rights as the goal of Islamic law (maqasid sharia) for the benefit of mankind. This study recommends that an in-depth analysis of human rights from various approaches and aspects be carried out in order to present a more solution theory and create new knowledge that enriches the treasures of Islamic knowledge